Country Partnership Framework for Mongolia for the Period FY21-FY25 - World Bank Group (World Bank, Washington, DC, 2021)
The year 2021 marks the 30th anniversary of the partnership between the World Bank Group (WBG) and Mongolia (1991-2021). This Country Partnership Framework (CPF) covers the period of FY21-25 and is timed to align with the mandate and development program of the government after the June 2020 parliamentary elections. The CPF is anchored in Mongolia’s long-term development strategy, Mongolia Vision 2050, and aligned with the Guidelines on Economic and Social Development (2020-2025) and the Government Action Plan (2020-2024), adopted by the newly elected parliament. The CPF has been informed by the 2018 Mongolia Systematic Country Diagnostic (SCD) and other key analytical work including a 2020 Country Economic Memorandum (CEM), the CPS Completion and Learning Review (CLR), and two rounds of consultations and a client survey with stakeholders in Mongolia.